SOME PROPERTIES OF FIBERBOARD MANUFACTURED FROM BEECH FIBER AND CHESTNUT SAWDUST (Innovation in Woodworking Industry and Engineering design, 2026)
In this study, some properties of medium density fiberboard (MDF) manufactured from mixtures of beech (Fagus orientalis) fiber and different ratios of chestnut (Castanea sativa Mill.) sawdust were investigated. The mixture ratios of fiber and sawdust were 85:15 %, 80:20 %, 75:25 %. Urea formaldehyde (UF) and melamine-urea formaldehyde (MUF) were used as resins. Water absorption (WA), thickness swelling (TS), surface roughness parameter (Rz), color change (∆E*) values were determined for MDF panels. Consequently, it was found that the WA, TS, ∆E* and Rz values increased with increasing sawdust ratio.